Paraná State coastline, Brazil: Response and Reconstruction facing Natural Disasters (Revista LIDER, 2020)
Are the cities damaged by hazards ready to access enforceable federal resources to disaster response and reconstruction measures? In general, are they correctly applied? What are the difficulties to the cities’ access to the enforceable federal resources? With basis in these questions, we proceeded to an analysis of the relationship between public institutions involved in the policy of prevention and response to disasters and the power of reality production, especially considering the last coastal disasters in Paraná State, considering the period between 2010 and 2012. The research hypotheses consider that the investigated cities had no political power to access the federal resources to disaster response and reconstruction measures. When they have the power, the destination of these resources is not correctly applied. With support in the collected data and theory, the research hypothesis was confirmed.